2014
DOI: 10.1039/c3ob41866a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tripeptide derivatized cyclopentadienyl complexes of technetium and rhenium as radiopharmaceutical probes

Abstract: We describe the syntheses of half-sandwich complexes of the type [(η(5)-Cp(CONH-R))M(CO)3] with M = Re or (99m)Tc. The R group represents different tri-peptides (tpe) which display high binding affinities for oligopeptide transporters PEPT2. The (99m)Tc complexes were prepared directly from [(99m)Tc(OH2)3(CO)3](+) and Diels-Alder dimerized, cyclopentadienyl derivatized peptides in water. This approach corroborates the feasibility of metal-mediated retro Diels-Alder reactions for the preparation of not only sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…A previous study showed that small biomolecules can be conjugated to Thiele's acid to yield compounds of the form [(C 5 H 5 CONH‐R) 2 ] . Following this procedure, different linear tri‐peptide sequences such as Leu‐Gly‐Gly were coupled to (C 5 H 5 COOH) 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study showed that small biomolecules can be conjugated to Thiele's acid to yield compounds of the form [(C 5 H 5 CONH‐R) 2 ] . Following this procedure, different linear tri‐peptide sequences such as Leu‐Gly‐Gly were coupled to (C 5 H 5 COOH) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The rhenium complexes [Re(η 5 ‐C 5 H 4 COOH)(CO) 3 ] can be obtained along different pathways . Originally, [M(η 5 ‐C 5 H 4 COOCH 3 )(CO) 3 ] (M═Re, Tc) was synthesized from [MO 4 ] − by the so‐called double ligand transfer reaction in the presence of CrCl 3 and a ferrocene (Fc) derivative that provides the Cp‐system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the next generation of potential rhenium radiopharmaceuticals requires chelators which can stabilize the metal centre both in the low and high oxidation states [7]. Furthermore, these multidentate chelators should also cater for the inclusion of biologically active moieties which may aid in the target specific biodistribution of the metallopharmaceuticals [8,9].…”
Section: Introductionmentioning
confidence: 98%